(untitled) (Huellas, 2020)
This research questions the neoliberalization cycles of state policies from a perspective that investigates the governmentality built in times of capture of public instruments. The aim is to analyze the changes in the ProHuerta program in Argentina in the period 2015-2019, within an exclusive restructuring context. More specifically, the political rationalities and state administration technologies are considered from the study of the components of Special Projects (SP) and Local Supply Groups (LSG). For that purpose, research is based on a triangulation methodological approach, which uses primary information – field observation, semi-structured interviews with officials and technicians of the National Institute of Agricultural Technology (INTA from its acronym in Spanish) and the Ministry of Social Development (MSD) – and secondary information – scholarly literature, documents and public budgets. Without further political motivations identified by the decision-makers, the punctual budgetary boom registered by ProHuerta has been associated with reinforcing welfare policies under a neoliberal political rationality (orchard as an individual achievement, quality of self-produced food split from its social purpose).